An On-Ramp to Student Success: A Randomized Controlled Trial Evaluation of a Developmental Education Reform at the City University of New York. (December 2021) - Weiss, Michael J.; Scrivener, Susan; Slaughter, Austin; Cohen, Benjamin
Most community college students are referred to developmental education courses to build basic skills. These students often struggle in these courses and college more broadly. CUNY Start is a prematriculation program for students assessed as having significant remedial needs. CUNY Start students delay matriculation for one semester and receive time-intensive instruction in math, reading, and writing with a prescribed pedagogy delivered by trained teachers. The program aims to help students complete remediation and prepare for college-level courses. This article describes the results of an experiment at four community colleges (n ~ 3, 800). We estimate that over 3 years, including one semester that students spent in the program and two-and-a-half years after the program was complete, CUNY Start substantially increased college readiness, slightly increased credit accumulation, and modestly increased graduation rates (by increasing participation in CUNY's highly effective Accelerated Study in Associate Programs [ASAP]).